Estudo da resistência à corrosão intergranular do aço inoxidável austenítico f138 - perspectiva de desempenho após Deformação Plástica Severa (DPS) - Rodrigues, Rodolfo de Souza (Universidade Federal de São Carlos, 2018)
Austenitic stainless steels are widely used in heating and cooling circuits of thermoelectric and nuclear power plants (NPP) in the storage and reprocessing of nuclear fuels, mainly because they have good processability, high resistance to corrosion and creep. In particular in thermonuclear applications there is, however, the trouble of swelling caused by the nucleation of He voids and bubbles within the irradiated material and the increased sensitivity to intergranular corrosion due to the acceleration by diffusion of alloying elements in the material. Using severe plastic deformation (DPS) by the equal channel angular pressing (ECAP), an increase in the bondary area can be achieved as well as an increase in the density of dislocation enhancing He trapping in these regions. In relation to intergranular corrosion, the mechanism acting in most cases is the sensitization caused by precipitation in boundary grain of chromium-rich phases such as Cr23C6 and intermetallic precipitates. Increased plastic deformation (above 15%) can accelerate the sensitization process in austenitic stainless steels. In order to evaluate the effect of DPS on the corrosion resistance in oxidizing media, the ASTM 262 Practice C test was performed on a ASTM F138 steel after solubilization (1h at 1100oC), sensitization (240h at 850oC) and ECAP (7 passes at 300oC). Microstructural characterization was performed to analyze the sensitization process and to verify the corrosion mechanisms using Optical Microscopy (OM), Scanning Electron Microscopy (SEM) together with X-ray Energy Dispersion Spectroscopy (EDS), Transmission Electron Microscopy (TEM), Mapping of crystallographic orientation by diffraction patterns in MET, X-ray Diffraction (DR-X) and X-ray Excited Photoelectron Spectroscopy (XPS). It was verified that while the sensitized material underwent intergranular corrosion the solubilized and ECAP material were subjected to gerenal corrosion. The mass loss in HNO3 was larger for general corrosion than for intergranular corrosion. The passive film of the ECAP sample contained more Chromium III and Molybdenum than in the solubilized sample, and therefore presented higher resistance to corrosion in the HNO3 medium. The sensitized material presented precipitates with high concentration of chromium and molybdenum leaving the surrounding regions more susceptible to intergranular corrosion and by pites. The film formed on the surface of the sensitized samples presented higher amount of the Chromium VI oxide in relation to the solubilized samples and ECA7x. This oxide is less resistant to acid corrosion than Chromium III oxide. The passive film of the ECAP sample contained more Chromium III and Molybdenum than in the solubilized sample, and therefore presented higher resistance to corrosion in the HNO3 medium.
Study of resistance to intergranular corrosion of austenitic stainless steel f138 - performance perspective after Severe Plastic Deformation (SPD)
Keywords: Sensitização; Deformação Plástica Severa (DPS); Extrusão em Canal Angular (ECA); Corrosão Intergranular; Sensitization; Severe Plastic Deformation (SPD); Equal Channel Angular Pressing (ECAP); Intergranular Corrosion (IGC); Deformações (Mecânica); Deformations (Mechanics); Resistência de materiais; Strength of materials; Plásticos - Extrusão; Plastics - Extrusion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA